2007
DOI: 10.1002/app.26432
|View full text |Cite
|
Sign up to set email alerts
|

Fiber and web formation of melt‐blown thermoplastic polyurethane polymers

Abstract: The goal of this research was to determine the fiber and web properties of melt-blown (MB) thermoplastic polyurethane (TPU) polymer as dependent on the MB processing conditions. The relationships between the MB fiber properties and the MB process conditions, such as the die-to-collector distance and the velocity of the MB TPU fiber in the spin line, were measured and estimated on the basis of the air velocity and air temperature, respectively. Consequently, this study provided fundamental guidelines of heat, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
2
16
1
Order By: Relevance
“…It is shown that mean velocity decreases rapidly with increasing distance from the die until reaching the point of z = 50 mm. A maximum mean velocity of 183 m s -1 is obtained at the point of z = 6 mm, which is about 30 m s -1 higher than the maximum velocity measured by previous researchers [13][14][15][16]. Although air velocity in the region of 0 mm \ z \ 6 mm is not shown in this work, it is no doubt that fiber undergoes strong attenuation effect by the high-speed air velocity in this region.…”
Section: Fluctuation Of Temperaturecontrasting
confidence: 68%
See 2 more Smart Citations
“…It is shown that mean velocity decreases rapidly with increasing distance from the die until reaching the point of z = 50 mm. A maximum mean velocity of 183 m s -1 is obtained at the point of z = 6 mm, which is about 30 m s -1 higher than the maximum velocity measured by previous researchers [13][14][15][16]. Although air velocity in the region of 0 mm \ z \ 6 mm is not shown in this work, it is no doubt that fiber undergoes strong attenuation effect by the high-speed air velocity in this region.…”
Section: Fluctuation Of Temperaturecontrasting
confidence: 68%
“…Compared to the previous works [13][14][15][16]28], innovations of researching turbulent air flow field in this work were: (1) an advanced two-dimensional velocity probe instead of one-dimensional velocity probe was applied in hotwire anemometer for measuring the fluctuation of air velocity, (2) the fluctuation of air temperature was originally measured, which has not been reported until now, (3) the coupling effect between air velocity and temperature was also analyzed by processing the data of measurements. Figure 1 a Schematic of the process of slot-die melt blowing [21], b the structure of single-orifice slot die and, c the real single-orifice slot die used in this work.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…1) consists of a CO2 laser system (PIN-30R, Onizuka Glass Co., Ltd.) 1 Satellite Venture Business Laboratory 2 Faculty of Textile Science of Technology, Shinshu University, 3-15-1, Tokida, Ueda, Nagano 386-8567, Japan 3 KB SEIREN, LTD., 6-1-1, Shimokoubata-cho, Sabae, Fukui 916-0038, Japan Abstract: We have investigated the effect of the spinning conditions (the applied voltage, the laser power, the laser irradiation point, and the laser beam width) in laser-heated electrospinning, on the diameter of thermoplastic polyurethane (TPU) microfibers. The average diameter of electrospun TPU fibers decreased with decreasing applied voltage and increasing laser power.…”
Section: Laser-heated Electrospinningmentioning
confidence: 99%
“…Melt blowing is mainly used to manufacture TPU nonwovens [1][2][3][4]. Melt blowing is a simple process for forming fine fibers by blowing hot air at ultrasonic speeds, but it suffers from high variation in fiber diameter.…”
Section: Introductionmentioning
confidence: 99%